Comparative study of ionic currents and exocytosis in hair cells of the basilar and amphibian papilla in bullfrogs - Zhao, Jingjing; Yin, Ning; Li, Geng-Lin (Frontiers in Cellular Neuroscience, 2023)
Hearing organs in the peripheral of different vertebrate species are extremely diverse in shape and function. In particular, while the basilar papilla (BP) is elongated and covers sounds of both low and high frequencies in turtles and birds, it is round and responds to high frequencies only in frogs, leaving the low frequencies to the amphibian papilla (AP). In this study, we performed patch-clamp recordings in hair cells of both hearing organs in bullfrogs and conducted a comparative study of their ionic currents and exocytosis. Comparing to hair cells in AP with a large TEA-sensitive slow-activating K+ current (IK), those in BP exhibited a small 4-AP-sensitive fast-inactivating K+ current (IA). Furthermore, hair cells in BP exhibited a significantly smaller Ca2+ current with a more positive half-activation voltage (Vhalf) and a slower slope of voltage dependency (k). In response to step depolarization, exocytosis (Cm) in BP hair cells was also significant smaller, but the Ca2+ efficiency, assessed with the ratio between Cm and Ca2+ charge (QCa), was comparable to that of AP hair cells. Lastly, we applied paired-step depolarization and varied the interval in between, and we found the replenishment of synaptic vesicles was significantly slower in BP hair cells. Together, our findings suggest hair cells tuned to high frequencies in bullfrogs release less synaptic vesicles and recycle synaptic vesicles more slowly, allowing them to cope well with the large DC component found in their receptor potentials in vivo.